62.8k views
18 votes
Jordan was given the expression 2x2^-3 x 2^-5 How should he write the expression as a fraction? Describe the exponent rules Jordan should use to simplify the expression

1 Answer

7 votes

Answer:


2*2^(-3) * 2^(-5) =(1)/(128)

Explanation:

Given


2*2^(-3) * 2^(-5)

Required

Write as a fraction

To do this, Jordan has to apply the following rules

Negative Exponent rule:


a^(-m) = (1)/(a^m)

So, the expression is:


2*2^(-3) * 2^(-5) = (2)/(2^3 * 2^5)

To solve further, we apply the product rule of exponent


a^m * a^n = a^(m+n)

So, the expression is:


2*2^(-3) * 2^(-5) =(2)/(2^(3+5))


2*2^(-3) * 2^(-5) =(2)/(2^8)

Evaluate the exponents


2*2^(-3) * 2^(-5) =(2)/(256)

Divide the numerator and denominator by 2


2*2^(-3) * 2^(-5) =(2/2)/(256/2)


2*2^(-3) * 2^(-5) =(1)/(128)

User Eric Steinborn
by
5.7k points